Situated, Yet Silent: Data Relations in Smart Street Furniture. Issue 3 (3rd July 2022) - Gangneux, Justine; Joss, Simon; Humphry, Justine; Hanchard, Matthew; Chesher, Chris; Maalsen, Sophia; Merrington, Peter; Wessels, Bridgette
ABSTRACT: This article provides new evidence of the ways that smart cities materialize within specific sites and contexts through smart street furniture (SSF). Drawing on empirical data generated through mixed-method field research, the article examines the situated data relations that emerge in the context of the adoption of InLinkUK smart kiosks in Glasgow and Strawberry Energy smart benches in London. The concept of "silences" is proposed to analyze insufficiently articulated data relations resulting from gaps or absences in the use, design, and governance of this new type of urban furniture. The argument made is that data silences lead to failures to account for decisions and the deferral of responsibilities regarding the data aspects of these objects. It is suggested that an approach that focuses on "listening" to and "speaking" about data relations can enable dialogical forms of accountability, and realize the potential of SSF for citizens in local contexts.